Spondylodiscitis and Its Mimickers: A Pictorial Review - Claudia Lucia Piccolo; Alberta Villanacci; Federica Di Stefano; Nicoletta Fusco; Davide Roberto Donno; Massimo Cristofaro; Fabrizio Taglietti; Stefania Ianniello (Biomedicines)
Spondylodiscitis is an infection of the intervertebral disc, the adjacent vertebral body, and/or contiguous structures due to the introduction of infectious agent, usually by the hematogenous route. Imaging is crucial in assessing bacterial and tubercular spondylodiscitis, as well as their associated complications. Magnetic resonance imaging in particular can clearly depict osteo-structural changes in the vertebral body and the associated disc, as well as any soft-tissue complications, such as paravertebral abscess and/or epidural abscess, improving disease characterization and helping to recognize the agent involved. Nevertheless, other non-infectious diseases may mimic imaging appearances of spondylodiscitis and one should be aware of these conditions when interpreting MR images, which include Modic type I degenerative changes, ankylosing spondylitis, acute Schmorl’s node, porotic fractures, and spinal neuropathy arthropathy. This pictorial review aims at describing imaging findings of bacterial and non-bacterial spondylodiscitis, complications, and those pathologies that mimic these infections.